A Case of Pediatric Sternal Fracture Diagnosed by POCUS - Takaaki Mori; Sung Shin Teng (CINQUILL Medical Publishers Inc., 2023)
A previously healthy, 4-year-old boy visited our emergency department due to chest pain after a fall from a skate scooter. Physical examination revealed tenderness over the sternal body. Point of care ultrasound (POCUS) of the sternum demonstrated a discontinuation of a hyperechoic structure of the sternal cortex, suggesting a sternal fracture. POCUS did not detect intraperitoneal fluid, pericardiac effusion, or pneumothorax. Plain radiograph confirmed the diagnosis of isolated sternal fracture and the patient was discharged with conservative treatment. POCUS was useful not only in diagnosing a sternal fracture but also to rule out concurrent injuries.